Benefits of government green procurement involvement among small and medium enterprises (SMEs) government suppliers - Ismail, Suhaiza; Masron, Nurin Athilah; Zainol, Zaini (University of Malaya, 2025)
Research aims: The aims of this paper are two-fold. First, it aims to investigate the important benefits of government green procurement (GGP) involvement by small and medium-sized enterprises (SMEs). Second, it intends to examine the differences between the small and medium sized groups in relation to the benefits. Design/Methodology/Approach: The study uses a questionnaire survey on 126 respondents who are working with SMEs that are holding the MyHIJAU status. Using Statistical Package for Social Sciences (SPSS), the descriptive analysis and t-test were conducted. Research findings: The top five most important benefits of GGP involvement as perceived by the overall SMEs are ‘reduced environmental problems’, ‘improved supplier’s image’, ‘meeting environmental protection goals and targets’, ‘improved compliance of government environmental protection regulations’ and ‘contribution to the competitiveness of local industry’. In addition, there is no statistically significant difference between the small and medium enterprise groups in relation to importance of all the benefits. Theoretical contribution/Originality: This study provides valuable insights into benefits gained from SMEs’ involvement in GGP which ultimately ensures their sustainability